Penerapan Aplikasi Berbasis Andorid Untuk Meningkatkan Pengendalian Internal dan Penjualan Pada AUM PCM Gedebage - Erfan Erfiansyah; Sutadi Triputra; Bingky Aresia Landarica (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
MSMEs in Indonesia have become the most important pillar for the economic ecosystem. It is known that 99% of business actors in Indonesia are in the MSME sector. The MSME sector is one of the main pillars of Indonesia's economic fundamentals. In fact, during the 1998 economic crisis, the MSME sector contributed positively in saving the Indonesian economic ecosystem at that time. The same thing happened during the Covid-19 pandemic, the MSME sector has great potential to become an accelerator of national economic recovery, therefore an entrepreneurial model is needed that can adapt to technological advances. The purpose of this research is to determine the internal control in managing the sales of MSME Partners as well as implementing Android-based applications in improving the internal control of the sales of MSME Partners. The stages of this research were carried out by means of a depth interview approach and also collecting data from several subsequent literatures by planning, designing and coding in implementing an Android-based application that can be applied. The results show that Android-based applications can help PCM seafood stalls improve internal control on cash sales transactions, Android-based applications also help retail businesses that are still using the old way of serving customers more effectively and efficiently. This system changes old methods to new ones that can improve business processes where all reports are recorded automatically so that employees can serve customers more efficiently and effectively. The new business process makes customers satisfied because they don't have to wait longer to get the desired product. Business revenue also increases by using the system because new customers can find and buy products online so customers who can't go to shop can buy them from the app and people who don't know about business can find them on the internet and can buy the desired products in the system